An epidemiological study of Cyclospora cayetanensis in Nepalese people - Sherchand, JB; Sherchand, JB; Cross, JH (Journal of Institute of Medicine Nepal, 2007)
Background: Cyclospora cayetanensis is a coccidian parasite that causes recurrent gastroenteritis among children living under poor sanitary condition and adults from industrialized countries who lived or traveled in endemic developing countries. Materials and Methods: A total of 1842 stool specimens from gastroenteritis patients were examined between March 2005 to February 2006 and collected various types of faecal specimens from human, animals and samples of water and green leafy vegetables. Results: Of 1842 stool specimens collected from different areas of Nepal, 146 (7.9 %) were found to be positive for Cyclospora cayetanensis with the majority were from children 2-9 years of age. The highest rate of infections was found in the month of June; (31.6%). Cyclospora cayetanensis were found to be contaminated in green vegetables including leaves of basil, mint leaves, water sources and feces of domestic animals and these findings were presented in the paper. Conclusion: Cyclospora-like oocysts were isolated for the first time from the leaves of basil, a holy plant of Nepal and the study indicated that vegetarian people were also found highest rate (65.1%) of Cyclosporiasis. However, to obtain more evidence on the source of infection, specimens from rodents, birds, insects and domestic animals are need for an extensive study. Key Words: Cyclospora cayetanensis, oocysts The full text of this paper is available at Journal of Institute of Medicine website